Study of Efficacy and Safety of Acitretin as Monotherapy in the Treatment of Moderate to Severe Plaque Type Psoriasis - Sarkar, Sumitendra Kumar; Sen, Krishna Gopal; Mostofa, Md Kamal; Rahman, Md Habibur (Faridpur Medical College Journal, 2020)
Psoriasis is a chronic papulosquamous disorder with remissions and exacerbations. Varied estimates of the population prevalence of the disease in different parts of the world range from 0.1 - 3%. It is not uncommon in our country. Although there are no treatment options offering a complete cure, a number of options exist for providing symptomatic relief, inducing as well as prolonging remission. Various systemic therapies such as methotrexate, acitretin, cyclosporine, and biologic agents can be used. A review of pharmacokinetics, safety and a discussion of relapse rate establish acitretin, an aromatic retinoid as an efficacious, convenient, oral monotherapy for initial and maintenance of severe psoriasis. A prospective clinical trial was conducted to find out the efficacy and safety of acitretin as monotherapy in the treatment of moderate to severe plaque type psoriasis (PASI range 10-42). Thirty two clinically diagnosed cases of moderate to severe plaque type psoriasis attending the Skin and VD out patient department of Faridpur Medical College Hospital, Faridpur were selected randomly. Majority (46.9%) were between 61 to 80 years of age and only 3.1% patients were in the <20 years age group. The average age was 57.3 years and range was 19-90 years. Majority (68.8%) of the patients were male and 31.2% patients were female. The male female ratio was 2.2:1. After 8 weeks of treatment with acitretin PASI 50 and PASI 75 response rates were 55% and 24% respectively and after 12 weeks of treatment, PASI 50 and PASI 75 response rates were 75% and 50% respectively. As side effects of the treatment, 4(12.5%) patients developed alopecia, each of xerophthalmia and cheilitis was seen in 3(9.37%) patients, each of fatigue and pruritus was seen in 2(6.25%) patients and only 1(3.12%) patient developed myalgia. This study demonstrates that acitretin as monotherapy is effective and safe in the treatment of moderate to severe plaque type psoriasis. Faridpur Med. Coll. J. Jan 2019;14(1): 16-19